Production de biogaz et de compost a partir de la jacinthe d’eau pour un développement durable en Afrique sahélienne - Oumarou Almoustapha; Jeanne Millogo-Rasolodimby; Siméon Kenfack (VertigO)
In the urban park Bangr-Wéoogo of the commune of Ouagadougou (Burkina Faso) the proliferation of the water hyacinth threatens the conservation of the biodiversity. The application of the integrated fight did not permit the eradication. The aim of the study is to contribute to the installation of a protocol of management of Eichornia crassipes which associates the mechanical fight with valorization by the production of biogas and compost. The results show a significant production of biomass with a proportion of dry weight (MS) of 6.12%. The experiment, carry out with some discontinuous digesters of 200 liters using 60 kg of water hyacinth as substrate mixed with 20 liters of liquid manure bacterium méthanogènes, indicate a average of bio gas production of 1440 liters for 3,67 kg of dry matter of water hyacinth witch means 392,37 liters /kg/ MS. The composts resulting from these experiments contain average 0,75 kg of nitrogene compounds, 10,6 kg of phosphoric compounds and 1,1 kg of organic carbon. The application of this technology in the wetlands infested by E crassipes has several advantages: energy production, compost and control of the proliferation of the water hyacinth.